MEME: DAPATKAH MENINGKATKAN KEMAMPUAN SISWA DALAM MENULIS TEKS ANEKDOT? - Fajar - Gumelar (JSSH (Jurnal Sains Sosial dan Humaniora), 2018)
Writing anecdote text is a creative and productive process, meaning an ability that requires students to produce a product (writing) that aims to provide criticism/ satire accompanied by humor against an event that occurred. The fact that the ability to write anecdot text is still low, the difficulty in putting ideas and ideas into the main factor. The need for a model of learning with the use of media as a way to overcome these problems. Projects based learning assisted media meme are used based on literature review, which is a student-centered learning by applying the concept of the project (based on actual life that occurs) in order to solve the problem independently by using memes as a media that serves to clarify a message or content delivered. At the stage (1) the determination of fundamental questions about the events that occur (actual), (2) preparing the project plan (selection of data collection activities), (3) preparing a schedule (completion of activities), (4) monitoring project progress, (5) assessment of results, and (6) evaluation of experience (reflection of activities). This research aims to determine (a) the effectiveness of the model and (b) the effectiveness of the model in the experimental class (MIPA and IPS). The methodology used is a quasi experiment with 2 by 2 factorial research design. The results of research from data analysis, obtained (a) the difference in ability between the experimental class and control class students with N-gain experiments enter into medium category, while the N-gain controls enter into low category. (b) there is no difference ability in experimental class between MIPA and IPS class students. This shows that the model of Projects based learning assisted media meme effectively used in the class with the background of MIPA and IPS in SMA Negeri 15 Bandung. Keyword: writing anecdote text, project based learning, and media meme.